DESCRIPTION OF THE LEVEL OF SATISFACTION OF INpatient PATIENTS WITH PHARMACEUTICAL SERVICES IN KENDARI HOSPITALS, KENDARI CITY - Muharni, Muharni; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Pharmaceutical services at the Kendari City Regional General Hospital are one of the services that has an increasing number of patient visits every day. To keep patients choosing service products at the pharmacy, hospitals must be able to meet patient needs so that satisfaction arises. The research aims to analyze the level of patient satisfaction with pharmaceutical services at Kendari city regional general hospitals based on the expectations and reality of the services received by patients. The research design used in this study was deskription. The population in this study was 108 inpatients with a sample size of 75 respondents. Sampling was carried out using simple random sampling. The research method is a survey with a questionnaire instrumentData analysis using the difference test (gap). This research shows the results that the gap between expectations and reality in physical evidence is (-0.25), empathy (0-0.07), reliability (-0.11), assurance (-0.20) and responsiveness (- 0.47). It was concluded that the quality of pharmaceutical services (the dimensions of physical evidence, reliability, assurance and responsiveness) influenced the satisfaction of inpatients at the Kendari City Regional Hospital. Sequentially, the highest level of patient satisfaction is in the dimensions of responsiveness, physical evidence, assurance, reliability and empathy. This means that all dimensions of service quality must be made a top priority in efforts to improve the quality of service to patients Keywords: Quality of Service, Pharmacy, Patient Satisfaction